2015
DOI: 10.1007/s00792-015-0775-9
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction-based screening method applicable universally to environmental haloarchaea and halobacteria for identifying polyhydroxyalkanoate producers among them

Abstract: The existing techniques for detection of polyhydroxyalkanoates (PHA) in halophilic archaea/bacteria are either imprecise or require prior PHA production before screening. The proposed method involves amplification of the approximately 280-300 bp conserved region of Class III PHA synthase (phaC) gene of halophiles using the primers codehopCF and codehopCR (Han et al. Appl Environ Microb 76:7811-7819, 2010). In this study, the best reaction condition was ascertained after repeated trials. This developed method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…In the case of halophiles, existing PHA detection methods are not precise enough, frequently deliver false positive results, and/or need prior PHA synthesis before the screening. To overcome this shortcoming, Mahansaria et al [83] developed a new method based on amplifying the conserved gene region phaC, encoding for the Class-III PHA synthase of halophiles. This region is about 280-300 bp in size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of halophiles, existing PHA detection methods are not precise enough, frequently deliver false positive results, and/or need prior PHA synthesis before the screening. To overcome this shortcoming, Mahansaria et al [83] developed a new method based on amplifying the conserved gene region phaC, encoding for the Class-III PHA synthase of halophiles. This region is about 280-300 bp in size.…”
Section: Discussionmentioning
confidence: 99%
“…All phaC-positive strains produced PHA in nutrient-limited medium, whereas no PHA production was evidenced by the phaC-negative strains. The authors evaluated their new method as highly precise, because it enables eliminating false positive results from Nile Red staining, e.g., due to the accumulation of lipophilic inclusion products different to PHA [83].…”
Section: Discussionmentioning
confidence: 99%
“…Nile red staining was used for the identification of PHA-producing colonies growing on agar plates by UV light exposure, showing the presence of fluorescent colonies in many haloarchaeal species [ 31 ]. Mahansaria et al (2015) also reported the use of Nile red in the staining of growing colonies for the identification of PHA producers among halobacteria and haloarchaea, and in the visualization of fluorescence colonies with a UV transilluminator in addition to a polymerase chain reaction-based screening method, through the amplification of a conserved region of the Class III PHA synthase ( phaC ) gene [ 32 ]. Both works reported the use of Nile red to identify PHA-producing microorganisms; stained cells were not observed with fluorescence microscopy, but with a UV transilluminator.…”
Section: Discussionmentioning
confidence: 99%
“…Nile red has been widely used for the in vivo screening and identification of PHA-producing bacteria on agar plates through the observation of fluorescent colonies under UV light [ 23 , 24 , 26 ]. However, due to the lipophilic nature of Nile red and Nile blue A, they can occasionally bind unspecifically to other lipid inclusions, membranes, or cell envelopes and can lead to ambiguous results [ 31 , 32 ]. For this reason, staining with an additional fluorescence dye can be appropriate to co-localize PHA granules.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Halomonas constitutes a group of halophilic (salt tolerant) bacterial species that are capable of producing PHB as a potential energy sink, as well as to help coordinate life in an environment characterized by high osmotic stress [15], and other stressors [16]. To date there are 79 species within the genus with varying degrees of salt tolerance, typically in the range of 5 – 25% (w/v) NaCl, and differing metabolic phenotypes [17].…”
Section: Introductionmentioning
confidence: 99%